(untitled) (Hawai, 2007)
"The ice is melting in the north," writes Oren Lyons, Faithkeeper, Turtle Clan, Onanadaga Nation, in an oration to world leaders that begins this collection. His words are a call for humanity to heal a wound in our relationship to the natural world. They are also a powerful metaphor expressing the fragility and uncertainty of the future in general, the result of global declines in justice, equality, and civility, alongside rising local and national enmity, and the partition of peoples along religious, ethnic, racial, and cultural lines. In this collection, the editors turn to some of the world's most thoughtful authors - in fiction, essay, poetry, drama, and a traditional folk parable - to ask important questions about the future, to give us moral direction, individual courage, and a map toward reconciliation
Keywords: Fiction; Tiểu thuyết,Literary Criticism; Phê bình văn học